Interaction between aluminum exposure and ApoEε4 gene on cognitive function of in-service workers. (May 2023) - Wang, Shanshan; Xue, Yingjun; Zhang, Jintao; Meng, Huaxing; Zhang, Jingsi; Li, Xiaoyan; Zhang, Zhuoran; Li, Huan; Pan, Baolong; Lu, Xiaoting; Zhang, Qinli; Niu, Qiao
Abstract: The occurrence and development of cognitive impairment, the early stage of AD, may be affected both by factors of environmental (aluminum exposure) and genetic (ApoEε4 gene). But whether there is an interaction between the two factors on cognitive function is still unknown. To explore the interaction between the two factors on cognitive function of in-service workers. A total of 1121 in-service workers in a large aluminum factory were investigated in Shanxi Province. Cognitive function was assessed by the Mini-mental State Examination (MMSE), the clock-drawing test (CDT), the Digit Span Test (DST, including DSFT and DSBT), the fuld object memory evaluation (FOM), and the verbal fluency task (VFT). The plasma-Al (p-Al) concentrations were measured by inductively coupled plasma-mass spectrometry (ICP-MS) as an internal exposure indicator, and the participants were divided into four Al exposure groups according to the quartile of p-Al concentrations, namely Q1, Q2, Q3, and Q4. ApoE genotype was determined by Ligase Detection Reaction (LDR). The multiplicative model was fitted using non-conditional logistic regression and additive model was fitted using crossover analysis to analyze the interaction between p-Al concentrations and the ApoEε4 gene. Finally, a dose-response relationship between p-Al concentrations and cognitive impairment was observed, with the p-Al concentrations increased, cognitive function performance gradually becomes worse ( P trend ＜0.05), and the risk of cognitive impairment gradually increases ( P trend ＜0.05), mainly in executive/visuospatial impairment, auditory memory impairment (particularly the working memory impairment). And ApoEε4 gene may be a risk factor for cognitive impairment, while no association between the ApoEε2 gene and cognitive impairment is observed. Additionally, an additive but no multiplicative interaction between p-Al concentrations and ApoEε4 gene is observed, and when the two factors work together, the risk of cognitive impairment further increased, of which 44.2% can be attributed to the interaction effect. Graphical abstract: Image 1 Highlights: Plasma-Al was positively correlated with cognitive impairment. ApoEε4 gene may be a risk factor for cognitive impairment. An additive interaction between Al exposure and ApoEε4 gene was observed. 44.2% of cognitive impairment risk can be attributed to the two factors' interaction.